Anti-cancer mechanisms of diarylpentanoid MS17 (1,5-bis(2-hydroxyphenyl)-1,4-pentadiene-3-one) in human colon cancer cells: a proteomics approach - Hon, Kha Wai; Zainal Abidin, Syafiq Asnawi; Abas, Faridah; Othman, Iekhsan; Naidu, Rakesh (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Diarylpentanoids are synthesized to overcome curcumin’s poor bioavailability and low stability to show enhanced anti-cancer effects. Little is known about the anti-cancer effects of diarylpentanoid MS17 (1,5-bis(2-hydroxyphenyl)-1,4-pentadiene-3-one) in colon cancer cells. This study aimed to elucidate molecular mechanisms and pathways modulated by MS17 in colon cancer based on proteomic profiling of primary SW480 and metastatic SW620 colon cancer cells. Cytotoxicity and apoptotic effects of MS17 were investigated using MTT assay, morphological studies, and Simple Western analysis. Proteomic profiling using LC/MS analysis identified differentially expressed proteins (DEPs) in MS17-treated cells, with further analysis in protein classification, gene ontology enrichment, protein–protein interaction network and Reactome pathway analysis. MS17 had lower EC50 values (SW480: 4.10 µM; SW620: 2.50 µM) than curcumin (SW480: 17.50 µM; SW620: 13.10 µM) with a greater anti-proliferative effect. MS17 treatment of 1× EC50 induced apoptotic changes in the morphology of SW480 and SW620 cells upon 24 h treatment. A total of 24 and 92 DEPs (fold change ≥ 1.50) were identified in SW480 and SW620 cells, respectively, upon MS17 treatment of 2× EC50 for 24 h. Pathway analysis showed that MS17 may induce its anti-cancer effects in both cells via selected DEPs associated with the top enriched molecular pathways. RPL and RPS ribosomal proteins, heat shock proteins (HSPs) and ubiquitin–protein ligases (UBB and UBC) were significantly associated with cellular responses to stress in SW480 and SW620 cells. Our findings suggest that MS17 may facilitate the anti-proliferative and apoptotic activities in primary (SW480) and metastatic (SW620) human colon cancer cells via the cellular responses to stress pathway. Further investigation is essential to determine the alternative apoptotic mechanisms of MS17 that are independent of caspase-3 activity and Bcl-2 protein expression in these cells. MS17 could be a potential anti-cancer agent in primary and metastatic colon cancer cells.